Definition and Classification of ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Issues relating to the definition and classification of ADHD are outlined from the Departments of Pediatrics, Neurology, and Child Study, Yale University School of Medicine, New Haven, CT.